Effects of Test Taking Strategies on Mathematics Test Anxiety and Performance among Junior Secondary School Students in Bukuru, Nigeria - Okolo, Priscilla Uzoamaka; Kolawole, Susan Ayoade (NIU Journal of Social Sciences, 2021)
This study investigated the effects of test taking strategies on junior secondary school student’s mathematic test anxiety and performance in Bukuru Nigeria. The study was motivated by the observed problem of high anxiety exhibited by students of mathematics as soon as teachers announce that there will be a test as well as poor performance in mathematics. Researches also show that high anxiety results to poor performance. This was to validate the claim that training and counselling of students on how to be test wise will reduce mathematics test anxiety in students in the junior Secondary School. The study adopted a quasi – experimental design, specifically the non – randomized, pre-test, post-test control group design.  The population of the study was 2,812 and the sample consisted of 60 JS one student’s in one government secondary school in Bukuru. Two intact classes were used for the experimental and control groups. The experimental group was given training and counseling using test taking strategies while no treatment was given to the control group. Mathematics Test Anxiety Scale (MTAS) and Mathematics Achievement Test were used to collect data. Their reliability coefficients were 0.89 and 0.92 respectively. The techniques employed in answering the research questions and hypotheses were percentages, means, standard deviation and t – test for independent samples. The study revealed that in the experimental group training and counseling on test taking strategies reduced student’s anxiety level, and improved their performance. The implication is that teachers and counselors should be trained to also train their students on the use of test-taking strategies to enable students not be anxious before and during tests for a better performance and testing situations in mathematics and other subjects. Keywords : Test Taking Strategies, Mathematics Test Anxiety and Performance.